Utilization Of Glycerol By Product From Transesterification Of Waste Cooking Oil As A Cosurfactant In Nanocream Preparation - Rani, Zulmai; Julia Reveny; Urip Harahap (International Journal of Science, Technology & Management, 2021)
Waste cooking oil (used cooking oil ) is oil derived from leftover cooking oil for frying food. Waste cooking oil is still considered as waste by some people and waste cooking oil that should not be suitable for consumption is sometimes still widely reused in food processing, this can endanger health and reduce the nutritional value of food. In order to be used and have economic value, it is overcome by synthesizing waste cooking oil into glycerol so it can be used as cosurfactant. Besides as cosurfactant, this waste cooking oil glycerol also can be used for various chemical industies, foods, cosmetics, and pharmaceuticals industries. For cosmetic preparation, it can make a nanocream preparation. The purpose of this research was to utilize waste cooking oil into a glycerol which is used as a cosurfactant, to characterize the synthesis results based on IR Spectroscopy data and to formulate it to nanocream preparation. The research was conducted in an experimentally by making glycerol from side product of waste cooking oil. Separating glycerol process conducted by transesterification reaction. Glycerol of waste cooking oil by product was characterized with IR Spectroscopy and evaluated include organoleptic, glycerol contents, density, viscosity, ash content, and moisture content. Formulation of nanocream preparation using 30% of Tween 80 as surfactant, glycerol by-product as cosurfactant 7,5% concentration, and 20% of VCO as oil phase. The nanocream preparation was measured for its particle size with the aim of being able to determine the particle size of the formula to form nanoparticle size. The results showed that glycerol of waste cooking oil by product shows the presence of OH, CH-aliphatic, C=O carbonyl and C-O. particle size of nanocream preparation obtained was 397,76 nm. Based on the result of this research, the conclusion is glycerol of waste cooking oil by-product can form nano size with presence of glycerol as cosurfactant. The particle size of the nanocream preparation obtained was still in the nanocream requirement range, namely 20-500 nm.